The Image of the Other, The Turk, in the novel Safar Burlak: An Imagological Approach - Almuthaybiri, Adel Musaylih Salhan (Arts for Linguistic & Literary Studies, 2024)
This study adopts an imagology framework to explore the portrayal of the Other (the Turk) within the contemporary Saudi narrative as depicted in Maqbool Al-Alawi's novel Safar Burlak. It delves into the various representations of the Other (the Turk) within the text, examines the underlying motivations for such depictions, and explores the factors influencing the formation of these representations. Employing a cultural criticism approach, the research is structured with an introduction, a preface, two main sections, and findings. The preface contextualizes imagology within comparative literary studies and articulates its relevance to the research topic. The first section scrutinizes the portrayal of the Turkish Other (the ruler), while the second section examines the depiction of the Turkish Other (the soldier) in the novel. Ultimately, the study discerns that the portrayal of the Turkish Other in the novel is characterized by themes of occupation and colonization, with negative portrayals rooted in historical realities, events, and transgressions committed by the Turkish Other against the self during a specific period.